Anisotropic strain in epitaxial single-layer molybdenum disulfide on Ag(110). Issue 44 (9th November 2021) - Bignardi, Luca; Mahatha, Sanjoy K.; Lizzit, Daniel; Bana, Harsh; Travaglia, Elisabetta; Lacovig, Paolo; Sanders, Charlotte; Baraldi, Alessandro; Hofmann, Philip; Lizzit, Silvano
Abstract : Uniaxial lattice strain is introduced in the lattice of a MoS2 single layer epitaxially-grown on Ag(110). Growth on a substrate with different crystalline symmetry is thus a promising way to introduce uniform strain in TMDC single layers. Abstract : In this work we prove that ordered single-layer MoS2 can be grown epitaxially on Ag(110), despite the different crystalline geometry of adsorbate and substrate. A comprehensive investigation of electronic and structural features of this interface is carried out by combining several techniques. Photoelectron diffraction experiments show that only two mirror crystalline domains coexist in equal amount in the grown layer. Angle-resolved valence band photoelectron spectroscopy shows that MoS2 undergoes a semiconductor-to-metal transition. Low-energy electron diffraction and scanning-tunneling microscopy experiments reveal the formation of a commensurate moiré superlattice at the interface, which implies an anisotropic uniaxial strain of the MoS2 crystalline lattice of ca. 3% in the [11̄0] direction of the Ag(110) surface. These outcomes suggest that the epitaxial growth on anisotropic substrates might be an effective and scalable method to generate a controlled and homogeneous strain in MoS2 and possibly other transition-metal dichalcogenides.